1977
DOI: 10.1042/cs0530009
|View full text |Cite
|
Sign up to set email alerts
|

Renal Handling of Dibasic Amino Acids and Cystine in Cystinuria

Abstract: 1. The effect of intravenous infusion of L-lysine and L-arginine on the tubular reabsorption of dibasic amino acids and cystine was studied in normal individuals and in homozygous and heterozygous subjects with cystinuria. 2. The control subjects reabsorbed almost all filtered lysine and arginine until the filtered load was elevated about fourfold. With further increased loads the tubular reabsorption began to fall and tended to approach a maximum reabsorption rate. By contrast, the homozygous subjects could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In the present study the tubular reabsorption of lysine and arginine in the cystinuria patients did not rise as much as that of the control subjects and some of the reabsorption rates gave negative values at low filtered loads, whereas the tubular transport of each amino acid was done at a normal rate with a great increase of the filtered load, showing nearly the same finding as that obtained in the earlier experiments (Kato 1977). An explanation for this might be proposed.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the present study the tubular reabsorption of lysine and arginine in the cystinuria patients did not rise as much as that of the control subjects and some of the reabsorption rates gave negative values at low filtered loads, whereas the tubular transport of each amino acid was done at a normal rate with a great increase of the filtered load, showing nearly the same finding as that obtained in the earlier experiments (Kato 1977). An explanation for this might be proposed.…”
Section: Discussionsupporting
confidence: 79%
“…Dent and Rose (1951) postulated that the dibasic amino acids and cystine have a common transport system which is defective in cystinuria . Lysine or arginine infusion in man (Robson and Rose 1957;Kato 1977) increases the urinary excretion of other dibasic amino acids and cystine , supporting Dent and Rose's hypothesis. However, in vitro studies with renal cortical slices (Rosenberg et al 1962; Fox et al 1964) have shown that the dibasic amino acids have a common transport system that is not shared by cystine .…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Early studies in humans identified 2 transport systems for cystine: a high-Michaelis constant (K m ) system and a low-K m system. 2,3 A defective low-K m system results in excessive amounts of both cystine and dibasic amino acids in urine, whereas a defective high-K m system results only in excessive amounts of cystine in urine. Dibasic aminoaciduria without cystinuria also can occur, and may be due to a defect in a dibasic transport system that is not shared with cystine.…”
mentioning
confidence: 99%